Ampelopsin induces MDA-MB-231 cell cycle arrest through cyclin B1-mediated PI3K/AKT/mTOR pathway in vitro and in vivo - Meng Minjun; Yang Qiaolu; Ouyang Zhong; Yang Qingmo; Wu Xinyi; Huang Yufan; Su Yonghui; Chen Shuanglong; Chen Wenlin (Acta Pharmaceutica)
Breast cancer is one of the most common malignant tumors in women and it is the most frequently diagnosed cancer in the world. Ampelopsin (AMP) is a purified component from the root of Ampelopsis grossedentata. It is reported that AMP could significantly inhibit the proliferation of breast cancer cells. However, the antitumor mechanism against breast cancer has not yet been fully elucidated. The purpose of this work was to study the role of AMP against breast cancer MDA-MB-231 cells and to further investigate the underlying mechanism. PI3K/AKT/mTOR plays a very important role in tumor cell growth and proliferation and we hypothesize that AMP may inhibit this pathway. In the present work, the results showed that AMP could significantly inhibit the growth of breast cancer MDA-MB-231 cells in vitro and in vivo. In addition, treatment with AMP decreased the levels of PI3K, AKT and mTOR, as well as cyclin B1 expression, followed by p53/p21 pathway activation to arrest the cell cycle at G2/M. Moreover, it demonstrated a positive association between cyclin B1 and PI3K/AKT/mTOR levels. Importantly, this pathway was found to be regulated by cyclin B1 in MDA-MB-231 cells treated with AMP. Also, it was observed that cyclin B1 overexpression attenuated cell apoptosis and weakened the inhibitory effects of AMP on cell proliferation. Together, AMP could inhibit breast cancer MDA-MB-231 cell proliferation in vitro and in vivo, due to cell cycle arrest at G2/M by inactivating PI3K/AKT/mTOR pathway regulated by cyclin B1.